2022
DOI: 10.3832/ifor3871-015
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of land sensitivity to degradation using MEDALUS model - a case study of Grdelica Gorge and Vranjska Valley (southeastern Serbia)

Abstract: Land degradation is a complex issue caused by diverse drivers, each of which should be considered in the analysis of land sensitivity to degradation. This study identifies the areas most sensitive to land degradation in the Grdelica Gorge and Vranjska Valley, which are unique in terms of natural and socioeconomic conditions. Land-use changes and inappropriate land management have led to serious degradation in this region. The flexible and multifactorial approach of the Mediterranean Desertification and Land Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The ESAI utilizing the MEDALUS technique has provided valuable insights into the vulnerability of different regions to land degradation and desertification [ [18] , [19] , [20] , [21] , 49 , 51 ]. The results of the current study have been reported using a score system, which divides the locations into various groups and subclasses based on their quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ESAI utilizing the MEDALUS technique has provided valuable insights into the vulnerability of different regions to land degradation and desertification [ [18] , [19] , [20] , [21] , 49 , 51 ]. The results of the current study have been reported using a score system, which divides the locations into various groups and subclasses based on their quality.…”
Section: Resultsmentioning
confidence: 99%
“…It is made up of a comprehensive collection of indicators that provide a standardized framework for monitoring and measuring land degradation and desertification, with an emphasis on characteristics such as soil, climate, vegetation, and management index [ 17 ]. The MEDALUS model has been successfully used to quantify land degradation and desertification risk in numerous studies [ 9 , 15 , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] ].…”
Section: Introductionmentioning
confidence: 99%
“…To combine them straightforwardly, each quality indicator was classified in a range from 1 (low vulnerability to land degradation) to 2 (high vulnerability to land degradation), assigning equal weights to each layer. The model, accurately validated through extensive field measurements (e.g., [72]), has been successfully applied to case studies in other European and non-European countries [73][74][75][76][77]. The present study evaluated land degradation vulnerability in Italy in a time interval of 50 years (1960-2010) and, more precisely, at three time points (1960,1990, and 2010, see Figure 2), the only dates currently available to exploit the full model at a national scale with the whole range of requested input variables [78].…”
Section: Esa Approachmentioning
confidence: 99%